2010
DOI: 10.1002/clc.20744
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Angiographic Outcomes of Drug‐Eluting Stents in Patients With Large Vessel and Single Coronary Artery Lesion

Abstract: Background: The aim of this study was to evaluate and compare the clinical and angiographic outcomes of 3 drug-eluting stents (DES) in patients with large vessel diameter and single coronary artery lesions. Hypothesis: The efficacy of 3 DESs may be similar. Methods: A total of 411 consecutive patients who visited 3 university hospitals from June 2004 to December 2007 and had a single coronary lesion which was treated with the use of a DES that was 3.5 mm in diameter were enrolled in this study. Patients were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The drug-releasing profile of the SES was reported to be slower than that of the E-ZES stent 6) . Late loss and neointimal coverage were found to be similar between BMS and E-ZES 7,8) , whereas those of the SES were significantly less. These characteristics of E-ZES might contribute at least in part to the relatively rapid healing process observed in this case.…”
Section: Discussionmentioning
confidence: 82%
“…The drug-releasing profile of the SES was reported to be slower than that of the E-ZES stent 6) . Late loss and neointimal coverage were found to be similar between BMS and E-ZES 7,8) , whereas those of the SES were significantly less. These characteristics of E-ZES might contribute at least in part to the relatively rapid healing process observed in this case.…”
Section: Discussionmentioning
confidence: 82%
“…The present mean balloon diameter of the stent (near 3.50 mm) and postprocedural reference diameter (≥ 3.10 mm) indicated that large vessels were treated in the present cohort because the frequency of TLR after a bare-metal stent (BMS) was relatively low in these baselines. [21][22][23][24] Considering this background, the present study showed far better angiographic outcomes for BES compared to SES, because SES showed a prominent advantage for angiographic outcomes in large vessels compared to the contemporary BMS 23) and zotarolimus-eluting stent, 24) and because angiographic efficacy was equal in large vessels between SES and EES in terms of target vessel failure. 23) Accordingly, the present study is the first to show the efficacy of BES on midterm angiographic outcomes compared to SES after being used in a clinical setting.…”
Section: Discussionmentioning
confidence: 57%
“…Where the two stent varieties do seem to differ is in late loss, an end point not included in this 12-month outcome meta-analysis. Zotarolimus-eluting stents have been documented to demonstrate greater late loss than paclitaxel-eluting stents [ 2 , 3 , 8 ]. This study, however, did not find an increase in stent thrombosis with zotarolimus-eluting stents.…”
Section: Discussionmentioning
confidence: 99%
“…A total of seven end points were extracted from five studies [ 2 6 ]. End points studied were myocardial infarction (MI), major adverse cardiac events (MACE), cardiac death, all-cause death, stent thrombosis, target vessel revascularization, and target lesion revascularization.…”
Section: Methodsmentioning
confidence: 99%